Avel och fruktsamhet hos nordsvenska hästen - Strandman, Jennifer (2008)
The fertility of the North Swedish horse was investigated using a questionnaire. Data concerning altogether 73 North Swedish stallions and 213 mares used for breeding during the season 2005 were collected and analysed. The survey also included the analyses of 305 breeding case books, especially distributed for this study, from 27 stallions. The aim was to collect information on how the breeding was carried out in the North Swedish horse, and to learn what categories of mares that were covered and what routines were used in these farms. Breeding statistics from 1999 to 2004 was also analysed to complete the questionnaire.